(untitled) - Richards, Jack C. (Cambridge, U.K, 1998)
New Interchange is a multi-level series for adult and young-adult learners of English from the beginning to the high-intermediate level.
Keywords: English language,Tiếng Anh; Textbooks for foreign speakers,Sách giáo khoa cho người nói nước ngoài